Optimal directions for directional distance functions: An exploration of potential reductions of greenhouse gases - Benjamin Hampf; Jens J. Krüger (Technische Universität Darmstadt, Department of Law and Economics, 2013)
This study explores the reduction potential of greenhouse gases for major pollution emitting countries of the world using nonparametric productivity measurement methods and directional distance functions. In contrast to the existing literature we apply optimization methods to endogenously determine optimal directions for the efficiency analysis. These directions represent the compromise of output enhancement and emissions reduction. The results show that for reasonable directions the adoption of best-practices would lead to sizable emission reductions in a range of about 20 percent compared to current levels.
Keywords: C14; D24; Q54; 330; climate policy; nonparametric frontier functions; directional distance functions